Impact of seawall development to the Sulawesi fishermen community in Pambusuang Village - Muhammad Zulkifli, 1993- 610664 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Sains (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2017